The goal of our research is to determine some morphological indices and attributes of physical and technical ability of young footballers from 15-16years post game. - Abdelatif, Houar (Journal of Sport Science Technology and Physical Activities, 2025)
where we took a sample of 60 players with an average age (15.5 ± 0.50). The researcher has based on anthropometric easurements and tests measuring the attributes of physical and technical ability to compare between the different positions of the game. The research results revealed significant differences between the positions of the game in stature measurements, the supra-sternal height, acromial height point, the height of the radial point diameter of the distal thigh diameter distal leg, distal diameter of the foot, chest expiration, and all the attributes of the vertical jump perimeter, the reaction rate of 10m, and driving speed ball in space materialized (with eight ball). Although the results of this study showed that there are no statistically significant differences in measures of body weight and calf circumference, and the attributes of Vo2max (Cooper 12mn), running speed with and without the ball on 30m, flexibility Ishio-leg and ball control in specific endurance (30m ×5). By the end of this enquiry, the investigation recommend the Algerian coaches to guide young players to play according to their positions in the morphological profile and physical and technical capabilities, and train thes young players based on the requirements of each position of the game.